A longitudinal study of the relationship between dental caries and obesity in late childhood and adolescence. (30th October 2017) - Hall‐Scullin, Emma Patricia; Whitehead, Hilary; Rushton, Helen; Milsom, Keith; Tickle, Martin
Abstract: Objectives: To determine whether caries experience in late childhood (aged 7‐9 years) was predictive of adolescent obesity (ages 12‐16 years) to inform the use of a common risk factor approach (CRFA) for prevention. Methods: A cohort study was conducted in an area of North West England. Clinical assessment of caries took place using the same methodology at ages 7‐9 years and 12‐16 years. Body mass index (BMI) category was calculated from height and weight measurements using age and gender specific cut‐offs at 12‐16 years only. The association between dependent variable (BMI category dichotomized as underweight/normal and overweight/obese) and explanatory variables (baseline and follow‐up dental caries and sociodemographic status) adjusted for age, was assessed. Results: At baseline, 5, 470 (96.8 percent) participants took part and information was available for 2, 958 (54.1 percent) participants at follow‐up. Univariate analysis indicated that BMI category in adolescence was not shown to be significantly associated with: the presence or absence of caries in late childhood ( P  = 0.61); in adolescence ( P  = 0.06); gender ( P  = 0.91); or deprivation ( P  = 0.35). Multivariate logistic regression indicated that BMI category in adolescence was not predicted by caries in late childhood or adolescence, after adjusting for sociodemographic variables. Conclusion: Caries and obesity were highly prevalent in this population. Caries in childhood was not shown to be associated with obesity in adolescence and there was no cross‐sectional association between the two diseases in adolescence. A CRFA is not precluded, however, the results suggest that additional interventions, specific for each disease, are required to prevent obesity and caries.